EVALUASI TINGKAT KERUSAKAN PERKERASAN JALAN KECAMATAN BANGGAI SELATAN KABUPATEN BANGGAI LAUT - Pilemon Lamatio; Djoni Agustaf; Tendly S. Maki, (Sustainable Construction (SUSCON), 2024)
This research focuses on evaluating the level of road pavement damage in the South Banggai Subdistrict, Banggai Laut Regency. The analysis prioritizes pavement damage as the main focus. Data on road damage and conditions were obtained through measurements and field surveys, utilizing evaluation indicators as a measure of road performance. Sustainability and transportation safety are crucial aspects in road infrastructure management, particularly due to their direct connection to road user safety. The evaluation not only focuses on damage analysis but also explores construction aspects and risk management. Thoughtful maintenance planning, including in-depth technical studies, is considered essential in maintaining optimal road function. This research applies a holistic approach encompassing integrated analysis, measurement, and research methods to ensure sustainability and transportation safety. In this context, the author takes the initiative to research the evaluation of road pavement damage levels, with the expectation of providing an accurate overview and valuable recommendations for relevant stakeholders in planning road maintenance and rehabilitation in the future.